Análisis de la transferencia de carga entre un generador y barra infinita, mediante la utilización de un prototipo - Anaguano Salazar, Algenis Gabriel (2019)
In the present project a module was built, that allows synchronization and charge transfer between a synchronous generator and an infinite bus, which is implemented in Engineering Electrical laboratory of Technical University of Cotopaxi whose objective is to analyze and visualize the system behavior before diverse conditions of operation. Charge transfer was validated by configurations in star (Y) to 220V acording calculated and measured electrical parameters, determining that resistive charge with an impedance of 105.83Ω consumes an active power of 457.2W, likewise the inductive charge of 0.17H with an impedance of 66.84Ω it consumes -723.9VAR and a capacitive charge of 20μF with an impedance of -j132.63Ω provides 365.76VAR of total power to the system. In delta connection (Δ) to 220V, the resistive charge with an impedance of 146.67Ω consumes a power of 990.73W, in the same way the inductors with an impedance of 64.71Ω consume power of -2240.58VAR, and finally the capacitors when they maintain the same impedance only change the contribution of 1097.43VAR total system. Finally, a user manual and practical laboratory guides were developed so that students can develop and interact with the elements and equipment that are part of the charge transfer module.